Child-Friendly Teaching Approach for Arabic Language in Indonesian Islamic Boarding School - Akmaliyah, Akmaliyah; Hudzaifah, Yasir; Ulfah, Nisrina; Pamungkas, Muhammad Ibnu (Universitas Negeri Makassar, 2021)
Mastering Arabic language is essential for Muslims as the language serves as a fundamental tool to understand and implement Islamic values. It is due to the fact that sources of these Islamic values, as in al-Qur'an and Sunnah, are accessible primarily through Arabic language. Both formal and informal education undertakings to master the language are then encouraged in this community. In connection to the dissemination and internalization of child-friendly values, it is necessary that the teaching of Arabic be carried out within this framework. Using descriptive analysis as the method, this paper discusses how these values may work in an Islamic environment such as Darunajah Islamic Boarding School. Data collection is done through observation, in-depth interviews, library research, and triangulation. In this study, components of Arabic language teaching which include educators, students, material, learning processes and evaluation, are put in relation to child-friendly values. The study shows that formal teaching of Arabic in Darunnajah Islamic boarding school has been in line with the framework of child-friendly values, in the part of educators while dealing and manage their students, also in the part of the textbooks and teaching materials, their contents, oral drills and presentation, also in the part of learning and evaluation processes.